2020
DOI: 10.4012/dmj.2019-039
|View full text |Cite
|
Sign up to set email alerts
|

Nano-graphene oxide with antisense <i>vicR</i> RNA reduced exopolysaccharide synthesis and biofilm aggregation for <i>Streptococcus mutans </i>

Abstract: Streptococcus mutans (S. mutans) has been proved to crucial cariogenic pathogens. Antisense vicR RNA reduced the transcription of virulence genes and lead to a reduction in biofilm formation. In the current study, a graphene-oxide plasmid transformation system was developed using interacted GO-polyethylenimine (PEI) complexes loaded with antisense vicR-expressing plasmid (GO-PEI-ASvicR). The particle size distribution and zeta potential of the GO-PEI-based ASvicR were evaluated. Quantitative real-time PCR assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Also, the results of the present study showed that gtfC was more affected in the combination-treatment group than the other genes tested. Deletion of gtfC markedly reduces attachment to smooth surfaces by S. mutans 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, the results of the present study showed that gtfC was more affected in the combination-treatment group than the other genes tested. Deletion of gtfC markedly reduces attachment to smooth surfaces by S. mutans 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of biofilm-related genes are motA gene, encoding the element of the flagellar motor complex, the efaA gene, which plays an important role in the adhesion of bacteria to surfaces [ 46 , 47 ]. ASOs can also block two-component signal transduction systems, such as VicRK, that induce the gene expression for the synthesis of extracellular insoluble glucan, an extracellular matrix component of biofilms [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2020 Wu S. et al developed a graphene oxide (GO)-based plasmid transformation system using electrostatic interacted GO-polyethyleneimine (PEI) complexes loaded with antisense vicR plasmid (GO-PEI-ASvicR). They showed that GO-PEI could efficiently deliver ASvicR plasmids into S. mutans cells with excellent transcripts of ASvicR, significantly reducing biofilm aggregation and exopolysaccharide (EPS) accumulation [ 48 ]. It is worth noting that graphene-based coating on titanium surfaces can be successfully obtained by electrodeposition as shown by Jankovic A (2015), making it a feasible option for innovative titanium coatings.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the therapeutic efficacy and applications of the ASOs as mechanisms of inhibition to design therapies for bacterial infections. [74][75][76][77][78][79][80][81][82][83] A similar strategy of ASOs could be exploited against the MDR efflux system of K. pneumoniae. Versatility and high specificity of complementarity of the antisense oligonucleotides allow the generation of antisense drugs that disable resistance to antimicrobials and act as adjuvants to join the armamentarium to fight multidrug resistance.…”
Section: Antisense Oligonucleotidesmentioning
confidence: 99%